Individualization of Communal Rights: Implications of Changes in Customary Marriage Structures for Customary Land Ownership - Muh. Akbar Fhad Syahril; Johamran Pransisto; Wiwin Wiwin; Ayu Chairun Nisa; Arini Asriyani (Jurnal Litigasi Amsir, 2025)
This study examines the impact of changes in customary marriage structures on the individualisation of customary land rights, from communal to individual ownership, and its implications for the governance and protection of customary land in Indonesia's indigenous communities. Using normative legal methods, the study finds that modernisation and land certification policies encourage the fragmentation of collective rights into private rights, thereby posing risks to weakened social solidarity, ownership conflicts, and increased vulnerability to land exploitation. Although providing administrative legal certainty, individualisation has not been able to optimally accommodate customary values and the social functions of customary land. Therefore, synergy between customary law and national law is needed to create fair and sustainable agrarian regulations, ensuring the protection of customary rights while adapting to the socio-cultural dynamics of indigenous communities.